Mujāhadah Students: the Innovation of Student Quranic After-Memorizing at the Institut Agama Islam al-Quran al-Ittifaqiah - Muhammad Amin (Studi Multidisipliner: Jurnal Kajian Keislaman, 2023)
This study aims to examine the innovation of quranic after-memorizing through the mujāhadah program conducted by 49 students at the Institut Agama Islam Al-Quran Al-Ittifaqiah (IAIQI). The analysis used in this study is the analysis of the living Quran and social construction theory. The results showed that the mujāhadah program was an effort in maintaining memorization through three stages, namely mujāhadah ulā (confirmation), mujāhadah sāniah (fasting for 40 days), and mujāhadah sāliṡah (evaluation). The three stages are the legitimacy of giving the sanad which leads to three main chains, namely from the K.H. Nawawi Dencik, K.H. Magfur Ali, and K.H. Nawawi Abdul Aziz. This program is the result of externalizing the taḥfīẓ coaches at the Al-Ittifaqiah Islamic Boarding School as well as the leaders and teaching staff at IAIQI. The results of the externalization were institutionalized in the use of mujāhadah guidelines, IQT’s vision, and also the provision of scholarships for mujāhadah students. While internalization occurs in the process of absorbing the value of mujāhadah into the enjoyment of reading the Quran for the perpetrators, the desire of students to complete the three stages of mujāhadah, and the motivation of non-mujāhadah students to participate in memorizing the Quran.